After Popper, Kuhn and Feyerabend
XIX, 257 p.
Keywords: Some think that issues to do with scientific method are last century's stale debate; Popper was an advocate of methodology, but Kuhn, Feyerabend, and others are alleged to have brought the debate about its status to an end. The papers in this volume show that issues in methodology are still very much alive. Some of the papers reinvestigate issues in the debate over methodology, while others set out new ways in which the debate has developed in the last decade. The book will be of interest to philosophers and scientists alike in the reassessment it provides of earlier debates about method and current directions of research.